Persistence of SARS-CoV-2 in COVID-19 patients during the second wave of the pandemic in India - Arghya Das; Ashima Jain Vidyarthi; Salman Khan; Sheetal Singh; Kiran Bala; LaxmiTej Wundavalli; Manali Agarwal; Jaweed Ahmed; Amit Sehgal; Pragati Grover; Parwez; Maitrayee Narayan; et al. (Journal of Infection in Developing Countries)
Introduction: India witnessed the catastrophic second wave of COVID-19 during the summer months of 2021. Many patients with non-resolution of symptoms admitted to dedicated COVID-19 treatment centers required prolonged inpatient care which led to the unavailability of beds for other COVID-19 patients. The objective of this study was to determine the duration of SARS-CoV-2 positivity in moderate and severe COVID-19 patients requiring long-term pulmonary care as well as to find out the association between different variables with the persistence of the virus.